JURIDICAL ANALYSIS OF FINANCING CONTRACTS POST CONVERSION OF BANK NTB INTO BANK NTB SHARIAH - Yeni Idayana Attoyibah; Hirsanuddin; Djumardin (Transpublika Publisher, 2022)
Islamic banking shows great potential, this is indicated by the large number of conventional banks converting to sharia-based banks. The conversion of conventional commercial banks to Islamic commercial banks has its own terms and procedures because it has quite basic differences, especially in the characteristics between interest calculation and profit sharing. Likewise, regarding the legal consequences that arise after conventional commercial banks are converted into Islamic commercial banks, of course, they also have their own characteristics. This research aims to find out how legal certainty over the Post-Conversion Financing Contract of NTB Bank into Bank NTB Shariah. This type of research is normative juridical research. This research uses a statute approach. Sources of Legal Materials used are primary, secondary, and tertiary legal materials. The collection of legal materials is carried out by methods of documentation studies and literature studies. The material is analyzed descriptively. The agreement in the financing contract at Islamic banking system is identical to the agreement in the credit contract at conventional banks, because the agreement's concept still refers to the Civil Code's Book III on General Engagements. According to Article 1233 of the Civil Code, an engagement occurs as a result of an agreement or by legislation. However, it should be noted that while financing Islamic banks, they must adhere to the Islamic economic rules that govern all banking activities.